Influence of valve size on the hemodynamic performance of a tissue-engineered valved conduit in pulmonary position - Ferrari, Lorenzo; Cox, Martijn; Obrist, Dominik (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionTissue Engineering (TE) uses resorbable polymers to promote in-situ cellular growth, transforming the implant into a living valve. This study characterizes the three-dimensional flow field around TE valved conduits of varying sizes using a pulse duplicator with tomo-PIV imaging.MethodsThree Xeltis Pulmonary Valve (XPV) conduits (16, 18, and 20 mm) were tested under pulmonary conditions at a cardiac output of 5 L/min. Flow velocities, trans-valvular pressure gradients (TVPGs), effective orifice areas EOAs, mean and turbulent kinetic energies (mke and tke), and viscous shear stresses were measured proximal and distal to the valves.ResultsPeak bulk velocity was 0.5, 0.4, and 0.3 m/s, with local peak velocities reaching 2.3, 1.9, and 1.4 m/s upstream and 3.6, 3.1, and 2.5 m/s in the jet downstream of XPV16, XPV18, and XPV20, respectively. Respective EOAs were 1.02, 1.25, and 1.57 cm2. The flow field proximal to the valve conduits did not show any significant perturbations and tke was one order of magnitude lower than mke. As the flow passed the valve, mke increased by 152%, 175%, and 218% for XPV16, XPV18, and XPV20, respectively, while tke increased by 62%, 138%, and 161%. The respective probability of encountering elevated shear stresses (>10Pa) was 6%, 2%, and less than 1%.DiscussionThis work provides the first in-vitro experimental assessment of the XPV valve, along with an exploration of how valve size affects its hemodynamic performance. Results confirm that for a given hemodynamic condition, larger valves exhibit better performance showing lower flow velocities, TVPGs, kinetic energies, and stresses, along with higher EOAs.